Determinants of TB Officer Performance in the Discovery of New TB Cases in the West Pasaman Regency Area - Ria Mayerlisya; Bambang Setiaji (Jurnal EduHealth, 2024)
This research aims to analyze the situation of the influence of knowledge, attitudes, actions and motivation on the discovery of new TB cases in the West Pasaman Regency area in 2023 with a focus on efforts to improve officer performance, through training and active participation of officers. Based on the 2021 Global TB Report, it is estimated that there are 824,000 TB cases in Indonesia, but only 393,323 (48%) TB patients were found, treated and reported to the national information system. There are still around 52% of TB cases that have not been found or have been found but have not been reported. In 2022, data as of September for TB discovery and treatment coverage will be 39% (1 year TC target 90%) and TB treatment success rate will be 74% (SR target 90%). Based on the 2022 Health Profile, West Sumatra Province is in 13th place based on the notification rate of all tuberculosis cases per 100,000. This research uses quantitative methods to explore the influence of knowledge, attitudes, actions and motivation on the discovery of new TB cases, based on the latest data which shows the achievement of low cases far below target. In fact, according to data, the number of TB officers available and distributed throughout health facilities in West Pasaman Regency is 82 people. Therefore, it is necessary to follow up regarding the performance of TB officers in discovering new cases. The research results show that knowledge and action influence the discovery of new cases in the West Pasaman Regency area in 2023. Meanwhile, attitudes and motivation have no influence on case discovery.